The Samarinda City Ulama's Perception of Shariah Life Insurance - Nur, Ichsan; Materan, Materan; Rachman, Aulia (Islamic Economic Law Study Program, Faculty of Sharia Sultan Aji Muhammad Idris Samarinda Islamic State University, 2024)
This article investigates the existence of legal disputes among ulama regarding the use of life insurance. Some ulama believe that life insurance is gharar because it insures the human soul, while others believe that there is no difference between conventional life insurance and sharia life insurance. This study uses qualitative descriptive approaches in empirical research to gather data as it occurs in the field, based on the problems that are presented. Interviews and documentation techniques were used to get information from informants on the issue of utilizing life insurance in sharia insurance. The study's findings suggest that Nahdlatul Ulama and Muhammadiyah Ulama view purchasing life insurance as a means of preparing for potential future disasters, reducing their personal risk of financial loss, and honoring their life insurance claims rather than as a means of thwarting Allah SWT's will. Sharia is not a fund intended to reward a person's soul; rather, it is referred to as a contribution fund or compensation fund to make up for losses brought on by calamities that occur.